Prevalence of Exclusive Breastfeeding and Associated factors among young Women attending Mbarara Municipal Council Health Centre IV - Allion Asiimire (Student's Journal of Health Research, 2021)
Background: Exclusive breastfeeding for six months provides the nurturing, nutrients, and energy needed for physical and neurological growth and development. However, nearly 2 out of 3 infants are not exclusively breastfed for the recommended 6 months, a rate that has not improved in 2 decades In addition, efforts to increase EBF particularly in Uganda have stagnated, with the rate remaining the same for many years. There is limited documented information specifically at Mbarara Municipal Council Health Centre IV (MMC H/C IV ) regarding the prevalence of exclusive breastfeeding and associated factors among young women. This study is therefore aimed at assessing the prevalence of exclusive breastfeeding and associated factors among young women. Methodology: A health Centre-based cross-sectional study was conducted among 93 pregnant women attending a postnatal clinic at Mbarara municipal council health center IV. Information was collected using a structured question. The prevalence of exclusive breastfeeding was 31.2%. The following variables were found to be significantly associated with exclusive breastfeeding, marital status OR 3.798 (CI.381-8.484) P=0.045, monthly income OR 2.750 (CI.380-8.058) p= 0.033. Conclusion and recommendations: A low prevalence of exclusive breastfeeding was noted among young women attending Mbarara Municipal Council Health Centre IV. The factors associated with exclusive breastfeeding include marital status and monthly income.